Teoria da agência e franchising: evidência empírica para o caso brasileiro - Rigoni, Ramon Frigi (2015)
The present study has a twofold objective: (i) evaluate determinants of the franchising option as a company´s strategy growth model and, (ii) analyze how franchising contract terms are affected by risk sharing, incentive problems related to moral hazard and financial constraints problems. The discussion is based on the empirical approach proposed by Lafontaine (1992). The models are estimated using a database containing information on 350 Brazilian franchisors. The results suggest that moral hazard problems from franchisee side as well as risk sharing are relevant to the definition of royalty rate value. Particularly, in business where the franchisee effort has significant influence on the input quality of the services provided, the royalty rate tends to decrease. Our results fails to identify a negative tradeoff between risk and incentives. CConcerning the expansion strategy option, as expected by the theory, results indicate that firms tend to expand through franchising when agent effort is relevant. However, opposed to the capital constraint hypothesis, our findings suggests that decisions to adopt franchising as a growth strtategy are not related to capital restrictions.